(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
In many scientific field Such as archeology, forensics and many other, there arises a problem of Reassembling of Image fragment. The solution of such problem by human intervention takes a lot of time and sometimes it might be costlier. So to overcome this problem, we are working on a system which will automatically reassemble those image fragments to form original image. Thus we can make an efficient use of this system with the help of 2D image fragment and contour detection algorithms. Reassembling is divided into four types of techniques. 1) Content based image retrieval system is use to identify spatially adjacent fragment. 2) Dynamic programming technique to identify matching contour segment. 3) Identify optimal transformation to align matching contour segment and 4) overall image reassembling. Thus with the help of these algorithms an optimal transformation in contour can be detected. Doing automation in such work will certainly help in faster, efficient and patiently reassembling this image fragments